Lian Gong em 18 Terapias como estratégia de promoção da saúde e qualidade de vida em idosos - Loyane Cabral Carrusca (2024)
Population aging is a global reality, which has an impact on the health and economic sectors. Considering that, it is necessary to implement effective public policies aimed at achieving senescence with the lowest possible degree of senility. In this context, the National Health Promotion Policy emerges and supports the concept of Integrative and Complementary Practices, among them Lian Gong in 18 Therapies (LG18T) created to prevent and treat chronic diseases and musculoskeletal syndromes, being therefore considered a preventive and curative exercise. Public authorities must offer conditions, through policies and programs that allow aging with a better quality of life, where the elderly are able to perform their occupational roles autonomously and independently. Therefore, the LG18T can be an important action in this regard. This work aims to map, in scientific literature, evidence on the relation between the Chinese body practice LG18T and the improved quality of life in the elderly. Specifically, it sought to describe the benefits of practicing LG18T for the elderly, to demonstrate how the practice contributes to healthy aging and to identify references to the inclusion of LG18T practice in public health policies. This is an integrative study of literature review. The search was carried out in the Scielo, Pubmed, Virtual Health Library (VHL) and Periodical Portal of the Coordination for the Improvement of Higher Education Personnel (CAPES) databases, using the single descriptor “Lian Gong'' in all databases. The set of selected texts was described in their bibliometric aspects and analyzed according to content analysis. The bibliographic search resulted in a total of 247 texts, where 174 publications were indexed on the CAPES Periodicals Portal, 57 on the VHL platform, 06 on the Pubmed database and 10 on Scielo. After applying the exclusion criteria, a set of 21 articles were carried on for critical analysis and discussion. All published articles can be found in health journals, mainly in Public Health (38.0%) and Health Sciences (33.3%). None of the selected articles were found in the areas of Humanities or Social Sciences. In scientific literature, it was found that the benefits of the practice for healthy aging are: improvement in pain, benefits for physical health, benefits for mental health, improved socialization. There were also found challenges in evaluating the practice and in mentioning how it fits into public health policies.